Sistem Informasi Pendaftaran Bimbingan Proyek II Prodi Teknik Informatika Politeknik Kediri - Ariyanti, Whenty; Heriadi, Agustono (Jurnal Informatika dan Multimedia, 2017)
The process of registration of guidance proyek II in D3 Informatics Engineering Program Polytechnic Kediri through three (3) stage, which is to find and meet the supervisor, print registration form, and collect the file to the department office. Viewed from various angles, there are several disadvantages such as lecturers seeking time-consuming, cost-consuming printing, and time-consuming recording and energy in rewriting the participants guidance data proyek ii. Making the registration information system guidance proyek iiis using waterfall method for analysis activities up to the test phase. Stages performed on research activities here is the analysis, design, coding, and testing. For the maintenance phase is not implemented in this study.The result of this research is the system design and an information system for registration of guidance proyek ii for D3 Program of Informatics Engineering Polytechnic of Kediri. This system shortens the selection process without having to meet the lecturer in question and facilitate the recording activity for the administration